Heparanase induces tissue factor pathway inhibitor expression and extracellular accumulation in endothelial and tumor cells - Nadir, Yona; Brenner, Benjamin; Gingis-Velitski, Sveta; Levy-Adam, Flonia; Ilan, Neta; Zcharia, Eyal; Nadir, Erez; Vlodavsky, Israel (Thrombosis and Haemostasis, 2008)
Heparanase activity is implicated in cell invasion, tumor metastasis and angiogenesis. Recently, we have reported that heparanase stimulates tissue factor (TF) expression in endothelial and cancer cells, resulting in elevation of coagulation activity. We hypothesized that heparanase regulates other coagulation modulators, and examined the expression and localization of tissue factor pathway inhibitor (TFPI) following heparanase over-expression or exogenous addition. Primary human umbilical vein endothelial cells (HUVEC) and human tumor-derived cell lines were incubated with heparanase, or were stably transfected with heparanase gene-constructs, and TFPI expression and secretion were examined. Heparanase over-expression or exogenous addition stimulated TFPI expression by 2–3 folds. TFPI accumulation in the cell culture medium exceeded in magnitude the observed induction ofTFPI gene transcription reaching 5– to 6-fold increase. Extracellular accumulation of TFPI was evident already 60 min following heparanase addition, prior toTFPI protein induction, and correlated with increased coagulation activity. This effect was found to be independent of heparanase enzymatic activity and interaction with heparan-sulfate, and correlated with reduced TFPI levels on the cell surface. Data were verified in heparanase transgenic mice tissues and plasma. Interaction between heparanase and TFPI was evident by co-immunoprecipitation. Interaction of heparanase with TFPI resulted in its displacement from the surface of the vascular endothelium and in increased pro-coagulant activity. Thus, heparanase facilitates blood coagulation on the cell surface by two independent mechanisms:dissociation ofTFPI from the vascular surface short after local elevation of heparanase levels, and subsequent induction of TF expression.
Keywords: TFPI; heparanase; coagulation; endothelial cells; tumor